2019
DOI: 10.1186/s40795-019-0295-6
|View full text |Cite
|
Sign up to set email alerts
|

Magnitude and associated factors of wasting among under five orphans in Dilla town, southern Ethiopia: 2018: a cross-sectional study

Abstract: Background: About 24 million children across the world live without their parents. In resource-limited countries like Ethiopia, childhood malnutrition is common and intertwined with poverty. It is a leading cause of death for children contributing over half of child mortality in sub-Saharan Africa. Nevertheless; little is known about the prevalence of malnutrition and associated factors among under five age orphans, as most of the variable studies were geared towards under five children as wholesome. Method: A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 4 publications
(3 reference statements)
3
17
2
Order By: Relevance
“…In this study, the odds of acute malnutrition was 3.63 times higher among children from households with two or more under ve children compared to children from households with one or no other under ve children. This nding was consistent with studies done in Dilla and Hawassa towns, Southern Ethiopia (24,25).This could be related to sharing of resources available at home. When there are more children at home, they may not be able to get enough food required for their growth and development (12).…”
Section: Discussionsupporting
confidence: 92%
“…In this study, the odds of acute malnutrition was 3.63 times higher among children from households with two or more under ve children compared to children from households with one or no other under ve children. This nding was consistent with studies done in Dilla and Hawassa towns, Southern Ethiopia (24,25).This could be related to sharing of resources available at home. When there are more children at home, they may not be able to get enough food required for their growth and development (12).…”
Section: Discussionsupporting
confidence: 92%
“…Of these, 189 (52.4%) were female by sex, 202 (56%) were maternal orphan children, 160 (44.3%) were in the age category 48-59 months with a mean age of 42.55 months, 292 (80.9%) were in a household who had number of under-five children greater or equal to two, and 140 (38.8%) of orphan children care giver were not attend any formal education ( Table 1 ). Besides, the details of the socio-demographic characteristics of participants have been described elsewhere in an earlier study from the same research project [ 17 ].…”
Section: Resultsmentioning
confidence: 99%
“…Besides, the details of the socio-demographic characteristics of participants have been described elsewhere in an earlier study from the same research project [17]. storage.…”
Section: Socio-demographic Characteristics Of the Respondentsmentioning
confidence: 99%
“…This is in contrast to a study done in Hawassa and Dilla, Ethiopia, where about a quarter of the participants were orphans. It showed that children whose parents were not alive were more likely to be stunted [ 15 , 22 ]. Also, a study in Zimbabwe in 2007 revealed that maternal and paternal orphans had statistically significantly heightened risks of stunting [ 10 ].…”
Section: Discussionmentioning
confidence: 99%